Ciência e política na era das novas biotecnologias: uma análise do marco regulatório brasileiro à luz de outras experiências - Maya Mitre (2011)
This dissertation analyzes some of the core political and ethical challenges involved in the domestic and international regulation of modern biotechnology. More specifically, we consider the regulation of activities involving genetically modified organisms, cloning, andhuman embryonic stem-cell research in Brazil, the United States, the European Union and some of its member states. In this process of analysis, we examine how different countries, union of countries, and interest groups situated these products of modern biotechnology, forregulatory purposes, within the boundaries that supposedly separate science from politics or, alternatively, expertise from lay participation. We assume that, despite claims for the universality of science, the regulatory models studied reflect historical patterns of interaction between scientists and the State, and long-lasting perceptions on the role of specialized knowledge in society, as well as peculiarities of the institutional and political context of each country or union of countries.